Kabuki Make-up Syndrome – A Case Report with Electromyographic study - Sattur, Atul (J Clin Diagn Res, 2014)
Kabuki make-up syndrome (KMS), also called Niikawa-Kuroki syndrome reported in 1981, is a rare congenital disorder of unknown aetiology. It is know to occur in many other ethnic groups, though initially described in Japan. We report a 24-year-old girl of Asian origin diagnosed with Kabuki syndrome based on characteristic clinical features. It is characterized by distinctive facial features (eversion of the lower lateral eyelid, arched eyebrows with the lateral one-third dispersed or sparse, depressed nasal tip, and prominent ears), skeletal anomalies, Dermatoglyphic abnormalities, short stature. As per our knowledge there is no literature which gives information about the importance of electromyographic study in the diagnosis and treatment of the KMS. Hence, this report emphasizes on the role of the same.